2022
DOI: 10.1002/phar.2659
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of insulin dose adjustments when initiating hemodialysis or peritoneal dialysis

Abstract: Chronically uncontrolled hyperglycemia is the leading cause of end stage kidney disease (ESKD) necessitating dialysis. During times of transition to hemodialysis (HD) or peritoneal dialysis (PD), considerations must be given to insulin dosing adjustments for persons with diabetes (PWD) in efforts to maintain glycemic control. However, the literature is sparse with few clear and direct practical clinical recommendations for therapeutic insulin dosing adjustments in PWD and ESKD. The objective of this systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…During times of transition to hemodialysis or peritoneal dialysis, consideration must be given to insulin dosing adjustments for subjects with T1DM in efforts to maintain glycemic control. In a recent review by Blaine et al [ 15 ], it was concluded that during peritoneal dialysis, insulin may be administered subcutaneously, intraperitoneally, or with the dialysis fluid. Administration of insulin with dialysate may necessitate a dose increase of up to 30% [ 15 ].…”
Section: The Gh Igf-1 and Insulin Interplay In Type 1 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…During times of transition to hemodialysis or peritoneal dialysis, consideration must be given to insulin dosing adjustments for subjects with T1DM in efforts to maintain glycemic control. In a recent review by Blaine et al [ 15 ], it was concluded that during peritoneal dialysis, insulin may be administered subcutaneously, intraperitoneally, or with the dialysis fluid. Administration of insulin with dialysate may necessitate a dose increase of up to 30% [ 15 ].…”
Section: The Gh Igf-1 and Insulin Interplay In Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…In a recent review by Blaine et al [ 15 ], it was concluded that during peritoneal dialysis, insulin may be administered subcutaneously, intraperitoneally, or with the dialysis fluid. Administration of insulin with dialysate may necessitate a dose increase of up to 30% [ 15 ]. Providing the liver with insulin in the dialysate will restore the GHR expression in the liver.…”
Section: The Gh Igf-1 and Insulin Interplay In Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…People on dialysis are at an increased risk considering glucose fluctuations. It may be required to lower the basal insulin dosage by up to 25% on days of hemodialysis (HD) to avoid hypoglycemia [90]. People undergoing HD are usually advised to avoid short-acting insulins during and immediately before HD [91].…”
Section: B Chronic Kidney Diseasementioning
confidence: 99%
“…During peritoneal dialysis (PD), insulin may be administered SC, or along with the dialysis fluid. If insulin is administered along with dialysate, an increase of up to 30% may be necessary to minimize the effects of dextrose absorption for the PD fluids and for the loss of tubing and dilution [90]. Hence, the lowest possible dialysate dextrose concentration should be used as a PD fluid as much as possible [92].…”
Section: B Chronic Kidney Diseasementioning
confidence: 99%
“…88 However, insulin requirements are reduced in some patients because insulin resistance is ameliorated with PD initiation. 89,90 We note that continuous glucose measurement devices are presently not approved for dialysis patients. In addition, the use of icodextrin may interfere with certain incompatible glucose measurement or continuous glucose monitoring devices where the metabolites will be misread as glucose.…”
Section: Metabolic Complications Of Pdmentioning
confidence: 99%